3D reconstruction of light flux distribution on arbitrary surfaces from 2D multi-photographic images - Chen, Xueli; Gao, Xinbo; Chen, Duofang; Ma, Xiaopeng; Zhao, Xiaohui; Shen, Man; Li, Xiangsi; Qu, Xiaochao; Liang, Jimin; Ripoll, Jorge; Tian, Jie (Optics express, 2010)
Optical tomography can demonstrate accurate three-dimensional (3D) imaging that recovers the 3D spatial distribution and concentration of the luminescent probes in biological tissues, compared with planar imaging. However, the tomographic approach is extremely difficult to implement due to the complexity in the reconstruction of 3D surface flux distribution from multi-view two dimensional (2D) measurements on the subject surface. To handle this problem, a novel and effective method is proposed in this paper to determine the surface flux distribution from multi-view 2D photographic images acquired by a set of non-contact detectors. The method is validated with comparison experiments involving both regular and irregular surfaces. Reconstruction of the inside probes based on the reconstructed surface flux distribution further demonstrates the potential of the proposed method in its application in optical tomography.